Nano-Microemulsions of CaCO3-Encapsulated Curcumin Ester Derivatives With High Antioxidant and Antimicrobial Activities and pH Sensitivity - Wang, Lian; Wang, Xuefei; Guo, Zhiwei; Xia, Yajuan; Geng, Minjie; Liu, Dan; Zhang, Zhiqiang; Yang, Ying (Frontiers in Veterinary Science, 2022)
In this study, we synthesised nano-microemulsions of CaCO3-encapsulated curcumin ester derivatives of diverse mass ratios by using the solution casting approach. The structures, antioxidant and antimicrobial activities, physical properties, and pH sensitivity of these products were examined. Compared with microparticles of CaCO3, those of CaCO3@Cur-FA exhibited excellent antimicrobial and antioxidant properties. Response to pH was indicated through the release of Cur-FA from CaCO3@Cur-FA in solutions having different pH values. The results demonstrated that Cur-FA was released more quickly from CaCO3@Cur-FA at pH 5.5 than at pH 7.4. CaCO3@Cur-FA demonstrated good antioxidant capacities through its ability to scavenge ABTS+ and DPPH. These activities were three-fold more than those observed in CaCO3 microparticle control groups; additionally, the antimicrobial activity against Aspergillus niger and Escherichia coli increased by 40.5% and 54.6%, respectively. Overall, the microparticles of CaCO3@Cur-FA outperformed Cur-FA in terms of antimicrobial properties by inhibiting the growth of certain zoonotic pathogens.